Implementasi Peraturan Gubernur Sumatera Barat Tentang Penggunaan Alat dan Bahan Penangkapan Ikan di Perairan Danau Singkarak - Putri Kumala Sari; Sujianto (Journal of Social and Policy Issues, 2021)
This study focus on the implementation of government policies related to the use of fishing gear that is not environmentally friendly in the Singkarak Lake. The background of the problem in this study is the use of large enough fishing gear and the disruption of the balance and preservation of fish in Singkarak Lake, especially the typical fish of the lake, namely Bilih fish. The theoretical concept used in this research is the theory of implementation of Van Meter Van Horn's policy in Sujianto in 2008. The method used in this research is a descriptive qualitative approach with a case study method. Data Collection Technique in this study are observasion, interview and documentations.  The results in this study indicate that the implementation of the Regulations Governor Sumatrai West Number 81 Year 2017 about Use Tool and material Arrest Fish in waters Lake Singkarak has not been realized properly. The inhibiting factors in this research include socialization, my sources, and awareness of the fishing community.